The Cognitive School and The Learning School (Sekolah Kognitif dan Sekolah Pembelajaran) - Silalahi, Rohani Marsaulina; Tampubolon, Manahan (LPPM Institut Pendidikan Nusantara Global, 2025)
The cognitive stream emphasizes the importance of reasoning and interpretation in strategic actions by focusing on how people process information, create knowledge, and make decisions. On the other hand, the learning stream places strong emphasis on organizational learning, viewing it as a living and breathing entity that continuously adapts to its environment. This article examines the core ideas of both approaches and assesses their relevance to management practices. The article aims to provide deep insights into how strategies can be developed and implemented more successfully by integrating theories and models from the cognitive stream and the learning stream. This article offers practical guidance for improving organizational performance and gaining competitive advantage in a fast-moving business environment through a literature review. Based on the research findings, it can be concluded that the cognitive stream and the learning stream can produce successful outcomes through strategic processes and development.